PHYSICOCHEMICAL CHARACTERISTICS OF CARP (Osphronemus gouramy) FILLETS FROM DIFFERENT HABITATS - Syahputra, Muhammad Fikri; Desmelati, Desmelati; Sumarto, Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThe aim of the research was to determine the differences in physicochemical characteristic carp fillet from different habitats. The research method used in this study was a comparative experimental method with the T-test design, consisting of 2 treatments, namely carp from cages (ke) and carp from a pond (ko) with 3 replicated. So, there were 6 units of experimental units. The parameters measured in this study were sensory analysis (appearance, odor, and texture), physical analysis (edible portion, dressing percentage, and water holding capacity) and proximate analysis (protein, fat, water and ash content). The results of the analysis showed that different habitats on physicochemical characteristics had a significant effect on appearance, texture, edible portion, dressing percentage and water-holding capacity, while the odor values were not significantly affected. Based on the proximate analysis that ke treatment higher in protein content 13.45%, and ash content 5.02%, meanwhile, ko treatment higher in fat content 2.86% and water content 79.20%.Keywords: carp, different habitats, physicochemical characteristics